Broad-Spectrum-Beta Lactamase Secreting Enterobacteria Isolated from Healthcare Associated Infections at the Tsaralalana Mother University Hospital Center - Razafindrakoto, Ainamalala Catherine; Razanadrakoto, Ianja Iorenantsoa; Rahajamanana, Vonintsoa Lalaina; Razanakolona, Paulin Andrianjakasolo; Razanakolona, Lala Rasoamialy; Robinson, Annick Lalaina; Rasamindrakotroka, Andry (British Journal of Healthcare and Medical Research, 2025)
Healthcare -associated infectious(HAIs) represent a major threat to the quality of peadiatric care, especially when they are associated with multi-resistants germs. The main objective of this study was to determine the incidence of HAIs linked to EBLSE and the factors associated with their occurrence at the Tsaralalana Mother University Hospital Center (CHUMET.) A retrospective case-control study was carried-out over 5-year period. All patients suspected of having a bacterial infection from a 48th hour of admission, with a positive bacteriolgical examination for EBLSE were included. Controls were those with the same criteria but whose bacteriolgical examination was negative. Matching was based on age, period and hospital ward, with 1:2 ratio. Of 218 hospitalised patients aged <15 yaers with a documented with HCAI, 129 were due to EBLSE, with an incidence of 0,9%. A total of 53 cases were included in the study The media age of the patients was 2 months, with a predominance of neonates (n=34, 64,1%). Enterobacter sp et Klebsiella sp were most frequently detected.. Low birth weight [OR=3,05 ; CI 1,19-8,01 ; p=0,01], gastric tube feeding [0R=6,56, CI 2,19-19,62, p=0,0002] and oxygen therapy [OR= 9,21 ; CI 2,95-39,53, p=0,00004] were the risk factors identified. Monitoring, application and evaluation of control measures and IPC activities within pediatric hospital establishments constitue the cornerstone of thr fight against HAIs and quality of care.